Special workThe genetic diagnostics of primary cutaneous T-cell lymphomas. Part III: The comparison of abnormal cell clone incidence in cutaneous T-cell lymphomas using molecular method of TCRγ rearrangement and cytogenetic techniques - Sokołowska-Wojdyło, Małgorzata; Nedoszytko, Bogusław; Gleń, Jolanta; Zabłotna, Monika; Placek, Waldemar; Silny, Wojciech; Wąsik, Agnieszka; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
TCRγ genes rearrangement analysis has already become a standard diagnostic method in cutaneous T-cell lymphomas (CTCL). Chromosomal aberration analysis has been more commonly used in diagnostics of leukaemias and lymphomas. The aim of the study was to compare the frequency of neoplastic clone incidence in CTCL determined by cytogenetic and molecular methods (TCRγ genes rearrangement analysis). The skin, lymph nodes and peripheral blood from 31 patients (25 with mycosis fungoides, 3 with Sezary syndrome, 2 with CTCL CD30+, 1 with angiocentric NK/T cell lymphoma) were analyzed. The chromosomal aberrations in metaphase culture of peripheral blood lymphocytes from 27 patients with CTCL (17 – MF, 7 – SS, 2 C-ALCL, 1 – angiocentric T/NK cell lymphoma) were tested with GTG method. The TCRγ genes rearrangement in biopsies from 31 patients with CTCL (25 – MF, 3 – SS, 2 – C-ALCL, 1 – angiocentric NK/T cell lymphoma) were analyzed with PCR TGGE (polymerase chain reaction/temperature gradient gel electrophoresis) and PCR/HD-MDE-PAGE (PCR/Heteroduplex – MDE – Polyacrylamide Gel). TCRγ monoclonality was confirmed in 71% of patients with CTCL. Clonal chromosomal aberrations were found in 70.4% of CTCL cases. The results were comparable and confirmed the complementarity of both methods in diagnostics and monitoring of CTCL.